Efektivitas Konseling Kelompok untuk Mengurangi Feeling of Inferiority Siswa di SMP Negeri 2 Bukittinggi - Nur Aini; Syawaluddin Syawaluddin; Rahmi Rifalina (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Students who have a feeling of inferiority think they will be useless and look down on their abilities. This research was conducted at SMP Negeri 2 Bukittinggi, where the students always felt inferior, were easily offended by criticism or other people's words, were afraid before trying, felt less valuable, felt less useful, thought negatively about themselves. This research was conducted to reduce feelings of inferiority experienced by students. This research uses a quantitative experimental method with a one group pre-test and post-test design. The research subjects were students who had feelings of inferiority in class IX which were obtained based on the results of observations and interviews. The population in this study was class IX students. This research sample used a purposive sampling technique of class IX students who had a feeling of inferiority. The data analysis technique uses the Wilcoxon rank test. The research instrument used a feeling of inferiority questionnaire. The results of this research can be seen from the pre-test and post-test with a decrease in each student after carrying out group counseling services showing a value of 0.027 < 0.05, so it can be concluded that group counseling to reduce students' feelings of inferiority has proven to be effective.